Submarine Geomorphology (Springer Geology,, 2018)
This book on the current state of knowledge of submarine geomorphology aims to achieve the goals of the Submarine Geomorphology working group, set up in 2013, by establishing submarine geomorphology as a field of research, disseminating its concepts and techniques among earth scientists and professionals, and encouraging students to develop their skills and knowledge in this field. Editors have invited 30 experts from around the world to contribute chapters to this book, which is divided into 4 sections - (i) Introduction & history, (ii) Data & methods, (ii) Submarine landforms & processes and (iv) Conclusions & future directions. Each chapter provides a review of a topic, establishes the state-of-the-art, identifies the key research questions that need to be addressed, and delineates a strategy on how to achieve this. Submarine geomorphology is a priority for many research institutions, government authorities and industries globally. The book is useful for undergraduate and graduate students, and professionals with limited training in this field.